The Importance of Basic PPE Usage in Reducing the Risk of Occupational Diseases and Workplace Accidents at PT Standard Toyo Polymer (STATOMER): Pentingnya Penggunaan APD Dasar untuk Meminimalisasi Bahaya Risiko Penyakit dan Kecelakaan Kerja pada Karyawan PT Standard Toyo Polymer (STATOMER) - Ismarina; Hero Wirasmara Kusuma; Santi Sundary Lintang; Tubagus Aan Rohyani; Karina Gita Puspita; Lilis Muhlisa; M. Nur Khamid (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Occupational health and safety are crucial aspects of the working environment. To protect workers from the risk of occupational diseases, the use of personal protective equipment (PPE) has become a common standard across various industrial sectors. PPE serves as the first line of defense for workers against different workplace hazards, including chemical, physical, and biological contaminants. This community service activity aimed to minimize the risk of occupational diseases and workplace accidents among employees of PT Standard Toyo Polymer (Statomer) in Cilegon City in 2025. The implementation involved lecture sessions and practical demonstrations. There were no significant obstacles during the activity, as participants were highly active in discussions. All participants shared their opinions freely, without fear or hesitation, while remaining focused on the topic discussed. The employees’ knowledge and understanding of PPE usage can be considered good, as the company regularly provides in-depth training on the proper use of PPE and explains its true benefits and functions in ensuring safety at work.